Induction of ferroptosis selectively eliminates senescent tubular cells. Issue 9 (8th June 2022) - Liao, Chieh M.; Wulfmeyer, Vera C.; Chen, Rongjun; Erlangga, Zulrahman; Sinning, Julius; von Mässenhausen, Anne; Sörensen‐Zender, Inga; Beer, Kristina; von Vietinghoff, Sibylle; Haller, Hermann; Linkermann, Andreas; Melk, Anette; et al.
Abstract: The accumulation of senescent cells is an important contributor to kidney aging, chronic renal disease, and poor outcome after kidney transplantation. Approaches to eliminate senescent cells with senolytic compounds have been proposed as novel strategies to improve marginal organs. While most existing senolytics induce senescent cell clearance by apoptosis, we observed that ferroptosis, an iron‐catalyzed subtype of regulated necrosis, might serve as an alternative way to ablate senescent cells. We found that murine kidney tubular epithelial cells became sensitized to ferroptosis when turning senescent. This was linked to increased expression of pro‐ferroptotic lipoxygenase‐5 and reduced expression of anti‐ferroptotic glutathione peroxidase 4 (GPX4). In tissue slice cultures from aged kidneys low dose application of the ferroptosis‐inducer RSL3 selectively eliminated senescent cells while leaving healthy tubular cells unaffected. Similar results were seen in a transplantation model, in which RSL3 reduced the senescent cell burden of aged donor kidneys and caused a reduction of damage and inflammatory cell infiltration during the early post‐transplantation period. In summary, these data reveal an increased susceptibility of senescent tubular cells to ferroptosis with the potential to be exploited for selective reduction of renal senescence in aged kidney transplants. Abstract : Low dose treatment with a ferroptosis inducer selectively eliminates senescent tubular cells and improves aged organ quality in a murine kidney transplantation model.